Optimalisasi Dana BOS dalam Meningkatkan Kualitas Pendidikan di SDN 2 Padasuka - Selvina Yunnita Sari; Muhammad Farisy Ammaryafi; Yanuar Akbar Muhammad Hamzah; Tegar Wahyu Hidayat (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
BOS Funds are an important instrument in supporting basic education financing. This study aims to analyze the management and optimization of BOS Funds at SDN 2 Padasuka and identify the obstacles and solutions applied. The approach used is descriptive qualitative through in-depth interviews and analysis of RKAS 2024 documents. The results of the study indicate that fund management has followed the financial management cycle according to Permendikbudristek Number 63 of 2023, including planning, implementation, administration, reporting, and accountability. Funds are used for learning, teacher training, improving facilities, and developing extracurricular activities. The obstacles faced include late disbursement, low digital literacy, and limited flexibility in revising RKAS. The school overcomes this through training, coordination with agencies, and committee involvement. In conclusion, BOS Fund management is quite optimal but still requires strengthening in the use of technology and the participation of stakeholders.